A Multi-Mode Pattern Diverse Microstrip Patch Antenna Having a Constant Gain in the Elevation Plane - Karaçuha, K.; Çelik, F. T.; Helvaci, H. I. (Advanced Electromagnetics, 2023)
This study investigates a multi-mode pattern diverse microstrip patch antenna operating at 2.45 GHz. The study aims to have a flat top gain covering more than 900 in the elevation plane to provide equal service quality to everyone in the region of interest. In order to achieve such a crucial goal, the cavity model approach for the rectangular patches is employed. TM01 and TM02 modes are selected for the design since their corresponding radiation patterns are suitable for scanning a wide range. The superposition of boreside and conical (monopole-like) beams form a wide beam radiation pattern in elevation. Coupling between different modes is reduced by placing two radiators perpendicular to each other. In addition, the design aims to reduce both initial dimensions of the antenna by using fractalization, slotting, and perpendicular positioning techniques. These techniques reduce the original dimension of the design to less than its 60%. The simulation and experimental results reveal many similarities regarding the scattering parameters, radiation patterns, and gain. The scattering parameters, |S11| and |S22| at the operating frequency, are less than -10 dB, and the wide beam radiation pattern (more than 900) is obtained in the elevation plane.